2016
DOI: 10.2807/1560-7917.es.2016.21.21.30236
|View full text |Cite
|
Sign up to set email alerts
|

Changing characteristics of livestock-associated meticillin-resistant Staphylococcus aureus isolated from humans – emergence of a subclade transmitted without livestock exposure, the Netherlands, 2003 to 2014

Abstract: Since 2007, livestock-associated meticillin-resistant Staphylococcus aureus (LA-MRSA) has become the predominant MRSA clade isolated from humans in the Netherlands. To assess possible temporal changes, we molecularly characterised over 9,000 LA-MRSA isolates submitted from 2003 to 2014 to the Dutch MRSA surveillance. After an initial rapid increase with a peak in 2009 (n = 1,368), the total number of submitted LA-MRSA isolates has been slowly decreasing to 968 in 2014 and over 80% of LA-MRSA belonged to one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…; Bosch et al . ). More detailed phylogenetic analysis of the t899 strains alongside others from Europe showed that they belong to the poultry‐associated sub‐clade of CC398 (data not shown; J. Larsen, pers.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Bosch et al . ). More detailed phylogenetic analysis of the t899 strains alongside others from Europe showed that they belong to the poultry‐associated sub‐clade of CC398 (data not shown; J. Larsen, pers.…”
Section: Resultsmentioning
confidence: 97%
“…; Bosch et al . ). Taken together, these observations suggest handling contaminated raw meat is likely to play a minor role in the epidemiology of CC398 LA‐MRSA (EFSA (European Food Safety Authority) and ECDC (European Centre for Disease Prevention and Control) ; Larsen et al .…”
Section: Resultsmentioning
confidence: 97%
“…In the IHO household both the adult’s and the child’s scn -negative S. aureus t002 (ST5) isolates were multidrug-resistant MRSA. Because lineages of ST5 and ST398 have demonstrated a successful capacity for human colonization and infection in community and hospital settings (Bosch et al 2016; Hau et al 2015; Larsen et al 2015), these instances of within-household S. aureus concordance suggest the need for further research of potential human-to-human transmission in households with and without occupational livestock exposure. The potential for bidirectional S. aureus transmission between adults and children is also important to consider because the predominant LA-MRSA CC398 clone in the European Union (Bosch et al 2016) started in humans as a methicillin-susceptible S. aureus strain and subsequently developed methicillin resistance via adaptation and selective pressures in livestock (Price et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the scn gene has been shown to be highly mobile, with phage-mediated loss in an animal host and insertion in a human host potentially occurring in as little as 4 hr (McCarthy et al 2014; Thammavongsa et al 2015). S. aureus spa types that circulate in livestock also can evolve quickly and putative LA- S. aureus markers based on spa types, CCs (e.g., CC398 or CC9) and/or MLSTs may have uncertain specificity depending on regional and microbial selection factors (Bosch et al 2016; Hau et al 2015; Lahuerta-Marin et al 2016; Ye et al 2016b). …”
Section: Discussionmentioning
confidence: 99%
“…31 In Europe, mecCpositive MRSA isolates (CC130 and t528) were described in captive mara (Dolichotis patagonum) at Copenhagen Zoo 32 while none of the 93 different mammals (40 species and 19 families) investigated at the Royal Zoological Society of Antwerp were MRSA positive. 33 Although isolation of MRSA CC398 or LA-MRSA is common among farmers (particularly pig farmers) in northern Europe, recent studies indicate a change in its epidemiology with an increasing number of colonizations in people without livestock contact, 34,35 which highlights the importance of identifying uncommon hosts that can act as potential reservoirs.…”
Section: Discussionmentioning
confidence: 99%